Qualitative Method of Salmonella Screening, Identification and Confirmation in Shrimp Matrices using Loop-mediated Isothermal Amplification Method, Enzyme Linked Immuno Fluorescent Assay and Standard Conventional Method - Shimna, Anikkadan; Levina, Tresa (Asian Journal of Biological and Life Sciences)
Contamination due to Salmonella in seafood processing have become greatest threat today. Effective monitoring and testing methodology used to get highest recovery of Salmonella to conform the requirements of Hazard Analysis Critical Control Point is a greatest challenge in today’s world. These challenges can be effectively addressed if the conventional detection methods which are labor-intensive and time-consuming shall be replaced by more rapid and highly sensitive methods. Study was doneto identify natural seafood contamination by Salmonella on raw freshly harvested Litopenaeus vannamei shrimp matrices and individually quick frozen Litopenaeus vannamei shrimp matrices. Study showed fastest recovery and accuracy with LAMP methodology (3MTM MDS System) than with ELFA (Bioemerieux- Vidas SPT) and Convectional method.
Keywords: 3M MDS system (Molecular detection system); ELFA (Enzyme Linked Immuno fluorescence assay; HACCP (Hazard Analysis Critical Control Point).; LAMP (Loop Mediated Isothermal Amplification) Method; Salmonella; USFDA (The United States Food and Drug Administration